Students’ Achievement in Speaking for Professional Context and Their Self Efficacy - Maria Ramasari (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2017)
This research aimed to find out whether or not there is a significant correlation between Students' Achievement in Speaking for Professional Context and their self-efficacy of English Education Research Program at STKIP-PGRI Lubuklinggau in the academic year 2016/2017. The researcher investigated this research through the descriptive correlation method. The data were analyzed by using Person Product Moment formula. Based on the result of data analyzed, it was found out that r-table was 0.288 and r-obtained was 0.546. Therefore, alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It meant that there was a positive correlation between Students' Achievement in Speaking for Professional Context and their self-efficacy. However, the strength of correlation level was considered insufficient classification. The conclusion showed that the students' self-efficacy had influenced students' speaking achievement.